PESANTREN EFFECTIVENESS: THE ROLE OF ORGANIZATIONAL CULTURE IN ENHANCING PERFORMANCE IN PESANTREN INSTITUTIONS - Manumanoso Prasetyo, Muhammad Anggung; Rahmatullah, Rahmatullah (STAI Ma'had Aly Al-Hikam Malang, 2024)
Abstract. The aim of this research was to plan and elucidate a framework of cultural structure for organization mainly for the advancement of its implementation. The object of the study was observed under the longitudinal research method and based on constructive organizational culture. The study employs a qualitative research design utilizing the grounded theory method. The key informants for this research comprise four individuals, namely the pesantren leader, deputy leader, and two teachers who serve as coordinators for student activities. Based on empirical data, Al Muslim has shown the potential to become a prominent pesantren in Aceh, utilizing a development model that prioritizes concentrated efforts in three key areas: work flexibility through institutional structural efficiency, curriculum revitalization and integration, and partnership development. Thus, in order to help attain the organizational object, the school administrators should develop an organizational culture.